Mobile Programming Untuk Siswa SMK Kesehatan Utama Insani Panongan Membuka Jendela Peluang Teknologi Dalam Dunia Kesehatan - Ade Putra Prima Suhendri; Meidy Fajar Wahyu; Yuda Samudra (AMMA : Jurnal Pengabdian Masyarakat, 2024)
In the current digital era, the integration of information technology has become crucial, especially in the healthcare sector. This activity highlights a mobile programming introduction program designed to enhance the technological understanding of students at the SMK Kesehatan Utama Insani Panongan. With the growing demand for skilled workers in mobile programming, the program aims to prepare students for an increasingly digital workforce. The program offers training on basic technological concepts, programming languages, and mobile application development processes. The hope is that participating students will gain a deep understanding and practical skills to compete and contribute in a healthcare sector that is becoming more integrated with technology. The benefits of this program are not limited to individual levels. With enhanced technological understanding, students have the potential to leverage technology in improving healthcare information management, patient monitoring, and health education. This means that the public can enjoy better and more efficient access to healthcare information. Moreover, the program fosters vital awareness of technology's role in the healthcare sector. It's not just about career opportunities but also about making meaningful contributions to the advancement of public health. Through this initiative, SMK Kesehatan Utama Insani Panongan strives to enhance the quality of student education and simultaneously make a positive contribution to the future progress of technology and healthcare. Overall, this activity underscores the urgency of equipping the younger generation with adequate technological understanding and skills to face the challenges of an increasingly digital and integrated workforce.